Interferon-Inducible GTPases in Host Resistance, Inflammation and Disease. Issue 17 (28th August 2016) - Pilla-Moffett, Danielle; Barber, Matthew F.; Taylor, Gregory A.; Coers, Jörn
Abstract: Cell-autonomous immunity is essential for host organisms to defend themselves against invasive microbes. In vertebrates, both the adaptive and the innate branches of the immune system operate cell-autonomous defenses as key effector mechanisms that are induced by pro-inflammatory interferons (IFNs). IFNs can activate cell-intrinsic host defenses in virtually any cell type ranging from professional phagocytes to mucosal epithelial cells. Much of this IFN-induced host resistance program is dependent on four families of IFN-inducible GTPases: the myxovirus resistance proteins, the immunity-related GTPases, the guanylate-binding proteins (GBPs), and the very large IFN-inducible GTPases. These GTPase families provide host resistance to a variety of viral, bacterial, and protozoan pathogens through the sequestration of microbial proteins, manipulation of vesicle trafficking, regulation of antimicrobial autophagy (xenophagy), execution of intracellular membranolytic pathways, and the activation of inflammasomes. This review discusses our current knowledge of the molecular function of IFN-inducible GTPases in providing host resistance, as well as their role in the pathogenesis of autoinflammatory Crohn's disease. While substantial advances were made in the recent past, few of the known functions of IFN-inducible GTPases have been explored in any depth, and new functions await discovery. This review will therefore highlight key areas of future exploration that promise to advance our understanding of the role of IFN-inducible GTPases in human diseases. Graphical Abstract: Highlights: IFN-inducible GTPases mediate host resistance to viral, bacterial, and protozoan infections. IFN-inducible GTPases localize to intracellular microbes and solicit defense pathways GBPs control inflammasome activation.